ANALISIS KINERJA KOPERASI BERDASARKAN TINGKAT KESEHATAN SESUAI PERMENKOP No 14/Per/M.KUKM/XII/2009 (Studi Kasus KSP Tirta Handayani, Desa Sumogawe, Kabupaten Semarang) - Pramono, Joko; Budiyati, Budiyati (AMONG MAKARTI, 2015)
AbstractCooperative is a pillar of the national economy which stand in line with other companies. To be able to compete with other financial institutions, the cooperative must have a healthy performance.The purpose of this study was to determine the performance of KSPTirta Handayani  terms of level of health based on the Regulation of the Minister of Cooperatives and SMEs No. 14 / Per / M.KUKM / XII / 2009, which includes elements of capital, asset quality, management, efficiency, liquidity, independence and growth as well as the identity of cooperatives. This study uses secondary data, ie data obtained from KSP Tirta Handayani year period 2011-2013 and analyzed based on the Regulation of the Minister of  Cooperatives and SMEs No. 14 / Per / M.KUKM / XII / 2009 healthy cooperatives.The analysis of research on the health level KSP Tirta Handayani show that in the period 2011 - 2013 predicate less healthy, because the results of the health assessment during the three periods the score achieved is in the range of 40 ≤ X <60. Analysis of the soundness of the KSP Tirta Handayani not only produce less healthy predicate, but over a period of 3 years in a row is also decreased health scores are scores 45.45 in 2011, in 2012 a score of 43.95, and in 2013 a score of 43.65 Keywords: capital, asset quality, management, efficiency, liquidity, independence and growth, the identity of cooperatives